Description of a new Brazilian species of Acanthoderini, new records in American Cerambycinae and Lamiinae, and a replacement name for a genus (Coleoptera, Cerambycidae) - Heffern, Daniel; Santos-Silva, Antonio (Zootaxa, 2023)
A new species of Acanthoderini is described from Brazil: Penaherreraus birai sp. nov. New records: Susuacanga rotundipennis (Bates, 1884) (Cerambycinae Eburiini) is recorded from the Mexican state of Jalisco; Psyrassa xestioides (Bates, 1872) (Cerambycinae, Elaphidiini) from the Mexican state of Oaxaca; Anisopodus dispar Bates, 1885 from Nicaragua (Lamiinae, Acanthocinini); and Lasiolepturges zikani Melzer, 1928 from Brazil (Pará) (Lamiinae, Acanthocinini). Variations in Urgleptes navarretei Santos-Silva, Nascimento, Botero & McClarin, 2021 are reported. Charlesella is proposed as a replacement name for Pygmaeopsis Schaeffer, 1908 (Coleoptera, Cerambycidae, Lamiinae, Desmiphorini), preoccupied by Pygmaeopsis Warren, 1907 (Lepidoptera, Geometridae).